A Biomechanical and Clinical Comparison of Midshaft Clavicle Plate Fixation: Are 2 Screws as Good as 3 on Each Side of the Fracture?. Issue 9 (23rd August 2017) - Larsen, Christopher G.; Sleasman, Brian; Chudik, Steven C.
Background: The standard of care for plating displaced midshaft clavicle fractures has been 6 cortices of purchase on each side of the fracture. The use of locking plates and screws may afford equivalent biomechanical strength with fewer cortices of purchase on each side of the fracture. Purpose: To compare the biomechanical and clinical performance of 3- versus 2-screw constructs for plating displaced midshaft clavicle fractures. Study Design: Controlled laboratory study/cohort study; Level of evidence, 3. Methods: Lateral fragments of simulated midshaft fractures in 10 pairs of cadaveric clavicles were randomly assigned to plate fixation with either 3 nonlocking screws or 2 locking screws. Cyclic tensile loads were applied along the long axis of the clavicle. The constructs were then loaded to failure with pullout forces applied parallel to the long axis of the screws. Additionally, clinical outcomes of patients who had midshaft clavicle fractures that were surgically repaired were retrospectively identified and compared; 21 patients were treated with 3-screw constructs and 20 with 2-screw constructs. Results: Biomechanically, there were no significant differences for cyclic displacement, stiffness, yield load, or ultimate load between groups. Forces required for screw pullout were considerably higher than physiologic forces experienced by a healing clavicle in vivo. Clinically, there were no significant differences in American Shoulder and Elbow Surgeons, Constant, visual analog scale, and Single Assessment Numeric Evaluation scores; complications; or mean time to union. Additionally, we found that the plates used in the 2-screw group were consistently shorter. Conclusion: Plate fixation of displaced midshaft clavicle fractures with 4 cortices of purchase with 2 locking screws demonstrated no significant differences biomechanically when compared with fixation with 6 cortices of purchase and 3 nonlocking screws. Clinically, there were no significant differences in outcomes or complications seen in patients receiving 2- or 3-screw constructs. Clinical Relevance: Clinical benefits of using the 3-screw construct for plate fixation include decreased surgical exposure, morbidity, and cost, and the use of shorter and noncontoured straight plates eliminates the extra time and technical difficulty associated with matching longer contoured plates to the complex morphology of the clavicle.